How Volatility Levels and Changes Affect the Underpricing and Aftermarket Performance of Initial Public Offerings - Kanto, Jukka (My University, 2010)
Going public is an important decision in the life of a company. Most companies that decide to go public do so via an initial public offering (IPO). Earlier studies have revealed that IPOs are prone to be underpriced, in that the share prices experience a substantial jump in the first trading day. Another established anomaly concerning initial public offerings is their long-run poor performance. In addition to IPO related literature, the role of a firm-specific risk is very important regarding this study. Previous studies document a significant increase in firm-specific volatility of stock returns over the past two decades. This increase has been documented to be even more dramatic for newly listed firms. The purpose of this paper is to investigate the effects of post-IPO firm-specific volatility level and volatility change on IPO-underpricing and post-IPO performance, cross-sectionally for new public companies in Finland. Three research questions are raised to address the focus of the study. First, what is the trend of post-IPO firm-specific volatility behavior? Second, how are the post-IPO return volatility levels and changes in return volatility related to the IPO underpricing? Third, how is the long-run post-IPO performance related to return volatility level and change? A negative association was found between the initial firm-specific volatility level and the post-IPO volatility change. The empirical evidence in this study indicates a strong association between high initial firm specific volatility and underpricing. The long-run performance evaluation reveals that the initial low volatility firms seem to outperform the high volatility firms in the first 240 trading days. Furthermore, low and increasing volatility firms are far better performers than the low and decreasing volatility firms.
Keywords: IPO; firm-specific risk; underpricing; long-run performance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|